La Modern Slavery Act y su impacto sobre las cadenas de suministros: la lucha contra las formas contemporáneas de explotación laboral y una propuesta de lege ferenda = The Modern Slavery Act and its effects on supply chains : an analysis of the struggle against modern labour exploitation and a lege ferenda proposal - Pereira Garmendia, Mario M. (Política criminal, 2023)
Located within the trafficking of human beings in labour exploitation, one of its worst manifestations is within the supply chain of multinational companies. Its prevention is the responsibility of International Law (for referring to systematic violations of ILO and United Nations standards) and National Criminal Law. Hence, a national normative corpus that exceeds the territoriality of said legal systems has begun to develop. It is the UK's Modern Slavery Act, one of the clearest examples. The scope of lege lata and lege ferenda that such legislation can achieve, as well as its comparison with the regime for preventing corruption and money laundering in the framework of international business, are the purposes of this research. Thus, our thesis advocates for creating an omission crime concerning those administrators and managers of multi-national corporations, when they intervene in said situations of labour exploitation through the breach of (qualified) duties of solidarity.